Analisis Pemilihan Perawatan Pada Sistem Bahan Bakar (Fuel Oil System) Kapal TB.BLORO 10 - Icuk Kurniawan; Mukhsin Al Amin; Arum Nurvitasari; Endah Wismawati (Proceedings Conference on Marine Engineering and its Application, 2023)
- Main Engine is one of the important compartments on the ship which is located in theengine room. Has a function as a propulsion driver and as the main propulsion engine of theship. With such an important position, scheduling maintenance on the Main Engine is veryimportant to do. Because if the main engine is not running, then there will be no operation ofthe propulsion system on the ship and it will definitely be very detrimental to the ship owner.This final project attempts to answer these demands by creating a maintenance schedule forthe main engine fuel system. In addition, the total operating costs which consist of running,maintenance and downtime costs will also be taken into consideration in determining themaintenance time. In this research of the analysis of choosing the best type of maintenance totake, namely, preventive maintenance for non-return valve components, quick closing valves,fuel injection pumps, and gate valves. Corrective maintenance is recommended for the fuel oiltransfer pump, injector nozzle, and fuel filter components. The cost of maintaining allcomponents is taken from the cost of preventive maintenance. The biggest cost is the fuelinjection pump component in each repair cycle with an expected minimum total cost incurredfor reliability 0.6 of Rp. 25,650,000 and the smallest cost for the fuel filter component in eachrepair cycle with an expected minimum total cost incurred for reliability 0.6 of Rp. .5,617,520.